The book of accidents : a novel - Wendig, Chuck (Del Rey, 2021)
"Haunted by their tragic pasts, Nate and Maddie Graves move back to their hometown with their son, Oliver, who becomes involved with a strange boy who has a taste for dark magic that puts them at the heart of a battle of good vs evil"--